Ultrathin Silicon Nanowires for Optical and Electrical Nitrogen Dioxide Detection - Dario Morganti; Antonio Alessio Leonardi; Maria José Lo Faro; Gianluca Leonardi; Gabriele Salvato; Barbara Fazio; Paolo Musumeci; Patrizia Livreri; Sabrina Conoci; Giovanni Neri; Alessia Irrera (Nanomaterials, 2021)
The ever-stronger attention paid to enhancing safety in the workplace has led to novel sensor development and improvement. Despite the technological progress, nanostructured sensors are not being commercially transferred due to expensive and non-microelectronic compatible materials and processing approaches. In this paper, the realization of a cost-effective sensor based on ultrathin silicon nanowires (Si NWs) for the detection of nitrogen dioxide (NO2) is reported. A modification of the metal-assisted chemical etching method allows light-emitting silicon nanowires to be obtained through a fast, low-cost, and industrially compatible approach. NO2 is a well-known dangerous gas that, even with a small concentration of 3 ppm, represents a serious hazard for human health. We exploit the particular optical and electrical properties of these Si NWs to reveal low NO2 concentrations through their photoluminescence (PL) and resistance variations reaching 2 ppm of NO2. Indeed, these Si NWs offer a fast response and reversibility with both electrical and optical transductions. Despite the macro contacts affecting the electrical transduction, the sensing performances are of high interest for further developments. These promising performances coupled with the scalable Si NW synthesis could unfold opportunities for smaller sized and better performing sensors reaching the market for environmental monitoring.